Behavioral Response of Weaned Pigs during Gas Euthanasia with CO2, CO2 with Butorphanol, or Nitrous Oxide - Enver Çavuşoğlu; Jean-Loup Rault; Richard Gates; Donald C. Lay (Animals, 2020)
The swine industry is often forced to euthanize pigs in the first few weeks of life due to injuries, hernias, or unthriftiness. The majority of pigs are euthanized using carbon dioxide (CO2) gas asphyxiation but concerns as to the humaneness of CO2 are increasing. This study compared the euthanasia of weaned pigs using N2O (N2O; n = 9) or CO2 (n = 9), at 50% and 25% min−1 exchange rate, respectively. In addition, we administered an analgesic prior to euthanasia with CO2 (CO2B) exposure as a third treatment (n = 9) to elucidate behaviors indicative of pain. Pigs in the CO2 and N2O treatments lost posture at similar times (latency of 145.0 ± 17.3 and 162.6 ± 7.0 s respectively, p > 0.10), while the CO2B treatment pigs lost posture the soonest (101.2 ± 4.7 s, p < 0.01). The pigs in the CO2B treatment made more escape attempts than the CO2 or N2O pigs (16.4 ± 4.2, 4.7 ± 1.6, 0.3 ± 0.2, respectively; p < 0.0004). However, pigs in N2O squealed more often than either the CO2 or CO2B pigs (9.0 ± 1.6, 2.8 ± 1.2, 1.3 ± 0.6, respectively, p < 0.001). Given the similar time to loss of posture and shorter time displaying open mouth breathing, N2O may cause less stress to pigs; however, the greater number of squeals performed by these pigs suggests the opposite. It was not apparent that any behavior measured was indicative of pain. In conclusion, N2O applied at a 50% min−1 flow rate can be an alternative to CO2 for pig euthanasia.